The influence of a 360-degree performance appraisal on labour productivity in an automotive manufacturing organisation - Robert W.D. Zondo (South African Journal of Economic and Management Sciences, 2018)
Background: South Africa’s (SAs) decline in labour productivity in the manufacturing sector is a cause for concern. The sector turns to employees for innovative productivity improvement initiatives. Employees need to know what activities they are currently performing that need to improve. This is where a 360-degree performance appraisal system plays a growing role. The 360-degree performance appraisal is a valuable tool that provides an opportunity for employees to work together to identify strengths and areas that need improvement.